Determinants of capital structure: Some UK evidences - Du, Xiaohui (2006)
Capital structure theories could be one of the most contentious issues in the theory of financial world. This study develops preliminary study to explain the cross-sectional variation in the capital structure of non-financial UK companies. We find that firm size, uniqueness are significant correlated to firms leverage level. The non-debt tax shield only significantly correlated to short term leverage. We fail to give significant support to the impact of firms profitability, volatility and growth opportunities on firm's borrowing behaviour. However, a strong industrial classification effect is founded in the UK firms and that result is consistent with Bennett & Donnelly (1993) and Bradley et al (1984). Furthermore, we find transaction cost have significant impact on firm's leverage policies. The correlations between empirical proxies and short term debt ratios are quite different from long term debt ratios.